The change of node importance and influencing factors in China's high-speed rail network. Issue 1 (April 2021) - liang, Xuedong; Liu, Rui; Lin, Shifeng; Yang, Lufan
Abstract: High-speed railway can change the geographical location of cities and enhance the importance of cities. This paper based on the complex network theory, combined with data of 2015-2019 year China's high-speed railway lines, constructs city as the node of the high-speed railway (HSR) network model, and probed the cities of PageRank in network, examined the high-speed rail network in the change of city node importance, analysed city node importance with time evolution and the regression model was used to determine the high-speed rail network in the city the affecting factor on the changes of node importance. The results show that: (1) Many cities in western China, such as Chengdu, Chongqing, have become significantly more important, while that of eastern coastal cities remains stable or even declines. (2)The level of economic development and population have the most obvious and positive influence on the importance of urban nodes. However, geographical location (latitude) and coastal area have negative effects on node importance.